Isolated tracheobronchial mucormycosis: Report of a case and systematic review of literature - Damaraju, Vikram; Agarwal, Ritesh; Dhooria, Sahajal; Sehgal, Inderpaul Singh; Prasad, Kuruswamy Thurai; Gupta, Kirti; Prabhakar, Nidhi; Aggarwal, Ashutosh N.; Muthu, Valliappan (Mycoses, 2023)
Background Isolated tracheobronchial mucormycosis (ITBM) is an uncommonly reported entity. Herein, we report a case of ITBM following coronavirus disease 2019 (COVID‐19) and perform a systematic review of the literature. Case description and systematic review A 45‐year‐old gentleman with poorly controlled diabetes mellitus presented with cough, streaky haemoptysis, and hoarseness of voice 2 weeks after mild COVID‐19 illness. Computed tomography and flexible bronchoscopy suggested the presence of a tracheal mass, which was spontaneously expectorated. Histopathological examination of the mass confirmed invasive ITBM. The patient had complete clinical and radiological resolution with glycaemic control, posaconazole, and inhaled amphotericin B (8 weeks). Our systematic review of the literature identified 25 additional cases of isolated airway invasive mucormycosis. The median age of the 26 subjects (58.3% men) was 46 years. Diabetes mellitus (79.2%) was the most common risk factor. Uncommon conditions such as anastomosis site mucormycosis (in two lung transplant recipients), post‐viral illness (post‐COVID‐19 [n = 3], and influenza [n = 1]), and post‐intubation mucormycosis (n = 1) were noted in a few. Three patients died before treatment initiation. Systemic antifungals were used in most patients (commonly amphotericin B). Inhalation (5/26; 19.2%) or bronchoscopic instillation (1/26; 3.8%) of amphotericin B and surgery (6/26; 23.1%) were performed in some patients. The case‐fatality rate was 50%, primarily attributed to massive haemoptysis. Conclusion Isolated tracheobronchial mucormycosis is a rare disease. Bronchoscopy helps in early diagnosis. Management with antifungals and control of risk factors is required since surgery may not be feasible.